A review of mucinous lesions of the breast. Issue 6 (18th May 2020) - Ginter, Paula S.; Tang, Xiaoyu; Shin, Sandra J.
Abstract: Mucinous lesions of the breast include a variety of benign and malignant epithelial processes that display intracytoplasmic or extracellular mucin, including mucocele‐like lesions, mucinous carcinoma, solid papillary carcinoma, and other rare subtypes of mucin‐producing carcinoma. The finding of free‐floating or stromal mucin accumulations is a diagnostic challenge of which the significance depends on the clinical, radiologic, and pathologic context. This article emphasizes the differential diagnosis between benign and malignant mucin‐producing lesions, with a brief consideration of potential mimics, such as biphasic and mesenchymal lesions with associated with mucinous, myxoid, or matrix material.